Case report: An infant boy with X-linked sideroblastic anaemia successfully treated by umbilical cord blood haematopoietic stem cell transplantation - Ma, Zhongyang; Li, Dongjun; Yang, Xue; Liang, Juan; Zhu, Yiping (Frontiers in Genetics, 2022)
X-linked sideroblastic anaemia (XLSA) is an inherited disorder caused by mutations in genes encoding proteins involved in the biosynthesis of haem. The pathogenic genes, as well as the pathogenesis and diagnosis of XLSA, have been fully elucidated in previous studies. However, only a few new advances have been made in managing XLSA in recent years, and blood transfusion remains the primary treatment. We report a case of umbilical cord blood haematopoietic stem cell transplantation in a male infant diagnosed with XLSA who was born with asphyxia due to severe anaemia. Early hepatic vein occlusion occurred after transplantation. However, this complication was rapidly controlled after active treatment, and the child’s quality of life improved significantly. Haematopoietic stem cell transplantation is a promising alternative treatment for XLSA.